Hydralazine inhibits ventricular tachyarrhythmias in an acquired long QT rabbit model. Issue 3 (17th July 2013) - Tsutsui, Kenta; Yamagishi, Satoshi; Kunishima, Tomoyuki; Hayami, Noriyuki; Murakawa, Yuji
Abstract: Background: Some cardioactive vasodilating agents inhibit ventricular tachyarrhythmias (VT) associated with acquired long QT syndrome (LQT). We tested whether a vasodilator without direct cardiac effect can eliminate abnormal repolarization‐related VT. Methods: The effect of hydralazine on the occurrence of VT was assessed in a methoxamine‐sensitized rabbit model of acquired LQT. To verify that VTs in this animal model are triggered by early afterdepolarization (EAD), monophasic action potential (MAP) on the left ventricular surface was recorded in open‐chest rabbits. Results: In control rabbits, combined administration of methoxamine and nifekalant frequently induced VTs (16/20, 80%). In contrast, VT occurred only in 2 out of 14 rabbits treated with hydralazine (14.3%, P <0.0001 vs. control). After the treatment, blood pressure was lower in the hydralazine group than in the control group (systolic pressure, 146±19 vs. 165±16 mmHg, P <0.0001; diastolic pressure, 54±10 vs. 101±11 mmHg, P <0.0001). EAD‐like hump was less frequently detected in hydralazine‐treated rabbits (2/10) than in saline‐treated rabbits (9/10, P <0.005). Presence of a hump was significantly related to the appearance of VTs ( P <0.05). Conclusion: Hydralazine inhibited VT in a rabbit LQT model. Vasodilation may have a therapeutic effect on abnormal repolarization‐related VT.